2022
DOI: 10.3390/logistics6030042
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Transport Logistics under Uncertainty with Simheuristics: Concepts, Review and Trends

Abstract: Background: Uncertainty conditions have been increasingly considered in optimization problems arising in real-life transportation and logistics activities. Generally, the analysis of complex systems in these non-deterministic environments is approached with simulation techniques. However, simulation is not an optimization tool. Hence, it must be combined with optimization methods when our goal is to: (i) minimize operating costs while guaranteeing a given quality of service; or (ii) maximize system performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Optimal transport corridor selection and its effectiveness is recommended as a benchmark to reflect the operating conditions of the selected transport corridors and/or transport modes due to disruption [53]. The results of the scientific literature review of related literature sources, related to similar tasks [54][55][56], indicated that a developed methodology of the transportation parameters evaluation is useful for the practical tasks and could be useful in many similar transportation cases. However, weight coefficients, which are used in developed methodology, could be discussed and further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal transport corridor selection and its effectiveness is recommended as a benchmark to reflect the operating conditions of the selected transport corridors and/or transport modes due to disruption [53]. The results of the scientific literature review of related literature sources, related to similar tasks [54][55][56], indicated that a developed methodology of the transportation parameters evaluation is useful for the practical tasks and could be useful in many similar transportation cases. However, weight coefficients, which are used in developed methodology, could be discussed and further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of solving routing problems is to design a set of routes that serve a set of geographically distributed points (cities, customers, etc.) at the minimal cost (minimum traveling distance or time) while respecting all the imposed constraints [5]. Routing problems have numerous applications that are applicable in real life.…”
Section: Preliminaries 21 Routing Problemsmentioning
confidence: 99%
“…Routing problems have numerous applications that are applicable in real life. The vehicle routing problem (VRP) and the traveling salesman problem (TSP) are popular problems that have attracted significant attention through the decades [5,6]. Table 1 provides a list of the routing problems that are referred to in this work.…”
Section: Preliminaries 21 Routing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sufficient number of publications are devoted to the justification of effective options for the transportation of bulk cargo, but, as a rule, the optimization of delivery routes is in the center of consideration [3][4][5][6][7]. Although most of the attention of researchers is focused on the delivery of small-lot cargoes, including the delivery of cargoes in containers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%